Questioning the no-touch discourse in physical education from a children's rights perspective. Issue 3 (3rd April 2017) - Öhman, Marie; Quennerstedt, Ann
Abstract : In this paper we question the rationality of 'no-touch policies' and offer an alternative approach to the matter of physical contact between teachers and students in the context of physical education (PE) in schools. Earlier research has drawn attention to how a discourse of child protection is starting to affect how physical contact is viewed in PE practice. The avoidance of intergenerational touch is increasingly justified by referring to the children's rights agenda. Here, arguments for 'no-touching' are linked to children's right to be protected from harm. In the paper we explore a children's rights-based viewpoint that supports the use of and need for physical contact in PE teaching by developing theoretical and practice-based arguments. An alternative children's rights perspective, based on rights theorising, is used to formulate the theoretical argument. Interviews with 16 PE teachers about their experiences of physical contact in their pedagogical work form the practice-based arguments. The two arguments provide a way of looking at intergenerational touch in education from the vantage point of children's human right to develop to their full potential, which can support a need for physical touch in pedagogical situations.